2009
DOI: 10.1158/1078-0432.ccr-09-1293
|View full text |Cite
|
Sign up to set email alerts
|

Novel Oligoamine Analogues Inhibit Lysine-Specific Demethylase 1 and Induce Reexpression of Epigenetically Silenced Genes

Abstract: Purpose: Abnormal DNA CpG island hypermethylation and transcriptionally repressive histone modifications are associated with the aberrant silencing of tumor suppressor genes. Lysine methylation is a dynamic, enzymatically controlled process. Lysinespecific demethylase 1 (LSD1) has recently been identified as a histone lysine demethylase. LSD1 specifically catalyzes demethylation of mono-and dimethyl-lysine 4 of histone 3 (H3K4), key positive chromatin marks associated with transcriptional activation. We hypoth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
191
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(197 citation statements)
references
References 41 publications
5
191
0
1
Order By: Relevance
“…LSD1 inhibited the proliferation of pluripotent cancer cells, including teratocarcinoma, embryonic carcinoma, seminoma or embryonic stem cells that express the stem cell markers Oct4 and Sox2, and colon cancer cells (Wang et al 2011). Treatment of the colon cancer cells with LSD1 inhibitors (such as SL11144) increases methylation at H3K4, decreases H3K9 methylation, and restores the expression of SFRP2, indicating the specificity of LSD1 and its inhibitors (Huang et al 2009). Its inhibition in neuroblastoma results in decreased proliferation in vitro and reduced xenograft growth (Schulte et al 2009).…”
Section: Polyphenolmentioning
confidence: 99%
“…LSD1 inhibited the proliferation of pluripotent cancer cells, including teratocarcinoma, embryonic carcinoma, seminoma or embryonic stem cells that express the stem cell markers Oct4 and Sox2, and colon cancer cells (Wang et al 2011). Treatment of the colon cancer cells with LSD1 inhibitors (such as SL11144) increases methylation at H3K4, decreases H3K9 methylation, and restores the expression of SFRP2, indicating the specificity of LSD1 and its inhibitors (Huang et al 2009). Its inhibition in neuroblastoma results in decreased proliferation in vitro and reduced xenograft growth (Schulte et al 2009).…”
Section: Polyphenolmentioning
confidence: 99%
“…17 One milligram peptide of histone H3 (residues [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] carrying one or two methyl groups at lysine 4 were incubated with 2 lg of GST-LSD1 in the absence or presence of Namoline. The reaction mixture was incubated in demethylation buffer for 4 hr at 37 C and analyzed by mass spectroscopy.…”
Section: Demethylase Assaymentioning
confidence: 99%
“…[7][8][9][10][11][12][13] However, these amine oxidase inhibitors including clorgyline, pargyline, tranylcypromine, polyamines and derivatives thereof, many of them do not selectively target LSD1 and therefore, limits their use as therapeutics owing to potential side effects. In this study, we found a novel and selective LSD1 inhibitor called Namoline by combining protein structure similarity clustering and in vitro screening.…”
mentioning
confidence: 99%
“…Further evidences on collaborative actions of LSD1 and DNMTs in epigenetic silencing of tumor suppressor genes were provided by Huang et al They showed that a combination of LSD1 inhibitors and a DNMT inhibitor has proven to be highly efficient in reactivating aberrantly silenced genes in cancer and led to profound inhibition of the growth of human colon cancer xenografts in nude mice. 21 The oncogenic potential of LSD1 could also be the result of the p53 antagonizing action of LSD1. LSD1 can control the tumor suppressor activity of p53 by directly demethylating a specific p53 lysine (Lys370me2/1), which is required for efficient binding to the transcriptional coactivator p53-binding protein-1.…”
Section: Lsd1/kdm1amentioning
confidence: 99%